Correlation and path analysis for yield and yield-related traits of potato (Solanum tuberosum L.) in Karnataka - Lavanya, K.S.; Srinivasa, V.; Ali, S.; Devaraju, D.; Lakshmana, D.; Kadian, M.S. (Springer, 2020)
Correlation and path analyses study on total tuber yield and yield attributing traits of nine CIP advance potato genotypes revealed that total tuber yield per plot had highly significant and positive association with marketable yield per plot, number of tubers per plant, dry matter and number of stems at 60 DAP both at genotypic and phenotypic level indicating the possibility of simultaneous selection for these traits to improve the tuber yield. It revealed that numbers of tubers per plant, marketable yield per plot, number of stems at 60 DAP and tuber weight were the most influencing factors to improve the tuber yield. Thus, these characters deserve greater weightage during selection for yield performance attribute.